The Use of Photogrammetry for Interactive, Three-Dimensional Modeling of an Open Reduction and Internal Fixation of the Elbow. (November 2020) - Isaacson, Dylan S.; Tanaka, Kara S.; Wang, Nigel K.; Storelli, Dora A.R.; Lattanza, Lisa L.
Abstract : We present our step-by-step guide to acquire and combine intraoperative photographs into three-dimensional models of surgical anatomy. We then apply our technique to model six steps in an open reduction and internal fixation of the elbow. Our protocol can be done with equipment and software retailing for under 500.